SupTech and RegTech initiatives: analysis of the basic characteristics and model risks - A. V. Kurnosov (Russian Journal of Economics and Law)
Objective: to analyze the SupTech and RegTech initiatives of central banks in the context of their essential characteristics and model risks.Methods: the work used a combination of methods of dialectical, empirical, comparative and logical research.Results: SupTech and RegTech technologies are defined; problems in the legal field existing within the framework of their use and ways to solve them are shown; model risks are assessed, in particular, the risks of adverse consequences resulting from the use of inaccuracies, errors, false assumptions and incorrect settings in models.Scientific novelty: the article identifies the model risks and suggests ways to reduce them, in particular, the risks of adverse consequences resulting from the use of inaccuracies, errors, false assumptions and incorrect settings; the work shows the need for a regulatory legal acts system and offers options for interpreting the models results.Practical significance: the main provisions and conclusions of the article can be used to develop a glossary, terms and definitions of SupTech and RegTech initiatives, the regulatory mechanisms and legal framework for their functioning, as well as to develop methods to reduce risks associated with the implementation and functioning of SupTech and RegTech initiatives.